2010
DOI: 10.2967/jnumed.110.080556
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Early 18F-FDG PET Interpretation in Diffuse Large B-Cell Lymphoma: Importance of the Reference Background

Abstract: This study investigated whether the reference background above which a residual mass is considered positive in the International Harmonization Project criteria should be modified for early 18 F-FDG PET evaluation. Methods: In 92 patients with newly diagnosed diffuse large B-cell lymphoma, the maximal standardized uptake value (SUVmax) was measured on postcycle 2 PET in the most intense residual mass (or, in the case of negative PET findings, in the area of most intense tumor uptake before therapy), in the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 18 publications
0
50
0
1
Order By: Relevance
“…24 Patients were scanned according to the routine protocol at participating PET centers. PET-2 scans were performed 12.3 ± 4.9 days (range, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] after the administration of the day 15 chemotherapy during the second ABVD cycle. Administered FDG activity was 359 ± 85 MBq (range, 85-699) for PET-0 and PET-2.…”
Section: Positron Emission Tomography Scanning and Review Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Patients were scanned according to the routine protocol at participating PET centers. PET-2 scans were performed 12.3 ± 4.9 days (range, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] after the administration of the day 15 chemotherapy during the second ABVD cycle. Administered FDG activity was 359 ± 85 MBq (range, 85-699) for PET-0 and PET-2.…”
Section: Positron Emission Tomography Scanning and Review Of Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Interim PET was reported to be a better predictor of prognosis than the International Prognostic Score (IPS) when carried out after two cycles of treatment with doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) in a joint Italian-Danish study (JID). 8 In a recent meta-analysis, overall sensitivity for the prediction of treatment outcome in Hodgkin lymphoma treated with ABVD ranged from 43% to 100% and specificity from 67% to 100%.…”
Section: -[mentioning
confidence: 99%
“…Even for Hodgkin lymphoma and DLBCL, there is, at present, still no official recommendation for interim restaging outside of clinical trials, even though some 18F-FDG-PET/CT studies have suggested that this imaging technique potentially enables an early outcome prediction, particularly when the FDG uptake in the liver is used as a reference (31). Therefore, a Deauville score of !4 was used as the criterion for residual disease in Hodgkin lymphoma and DLBCL on interim 18F-FDG-PET/CT, as previously recommended (33), whereas for all other lymphoma subtypes, the unmodified IHP criteria for PET were used, because the Deauville criteria have not yet been evaluated here.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is generally felt that for assessment of early response, particularly in risk-adapted therapeutic trials, it is preferable to refer to a background tissue (such as the liver) with a higher level of uptake than that of current international criteria that were designed for end-of-treatment evaluation. 13 As recently shown, the reproducibility of lymph node measurements is poorest below 20 mm, which leads to major discrepancies in FDG-PET interpretation 14 as the reference background changes. In 2009, an international workshop on interim FDG-PET 15 took place to reach a consensus on criteria for interim FDG-PET scans.…”
Section: Interpretation Of Pet Scansmentioning
confidence: 99%